Gerard Mercator´s Three Astrolabes - Turner, G. L´E. (ENDOXA, 2005)
No scientific instruments made by Gerard Mercator (1512- 1594), the great cartographer, were known to exist, though it is recorded that he made astrolabes and other brass artefacts. In early 1992, the present author identified an unsigned astrolabe in Florence as being made in Mercstor’s Duisburg workshop. By 1994, the 400th anniversary of Mercator’s death, two fiírther astrolabes had been identified as being by his hand. They are in museums in Augsburg and Brno. This paper describes the mcthod of identifícation of these unsigned instruments, culminating in the discovcry of Mercator’s monogram on the rim of the astrolabe in Brno.